Pterygoid Implant: A Graftless Approach for Maxillary Rehabilitation using TTPHIL-ALL TILT (Tall Tilted Pin Hole Placement with Immediate Loading) Technique (Global Journal of Medical Research, 2019)
Edentulism is a common dental problem in the elderly population. The maxillary posterior edentulous region offers a unique and challenging condition in implant dentistry. The maxillary posterior region presents with numerous anatomic complications in terms of bone quantity, quality, maxillary sinus pneumatization, and poor approachability. Most remarkable surgical approaches include sinus lift, bone grafting, pterygoid implant, considered as valid solutions to this problem. Pterygoid implants require lot of skill of the dentist and also is proven to be statistically superior. In this case series, the pterygoid implants placed and restored using TTPHIL (Tall Tilted Pin Hole placement with Immediate Loading)-ALL TILT ® technique in the patients with atrophic posterior maxilla are discussed.
Keywords: pterygoid implants; graftless solutions; immediate loading; TTPHIL-ALL TILTAE